2009
DOI: 10.1111/j.1574-695x.2008.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

A limited role for antibody in protective immunity induced by rCPAF and CpG vaccination against primary genitalChlamydia muridarumchallenge

Abstract: Mice deficient in B-cells (μmT mice) were used to evaluate the role of antibody in enhanced chlamydial clearance and reduction of pathology afforded by vaccination with recombinant chlamydial protease-like activity factor (rCPAF). Enhanced, but comparable, chlamydial clearance was observed in μmT and wild type (WT) mice after rCPAF+CpG vaccination. Chlamydia-induced pathology was present in mock-immunized animals, but at significantly greater levels in μmT than WT mice, whereas vaccinated μmT and WT mice exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
6
29
0
Order By: Relevance
“…However, even though anti-Chlamydia antibodies are able to neutralize infection in vitro (100,101), growing evidence shows that B cells may not be important for initial chlamydial infection but, instead, play an important role in the secondary memory response (102,103). Several possible mechanisms by which B cells modulate immunity during reinfection include antibody-mediated neutralization and opsonization (100) and antibody-dependent cellular cytotoxicity (ADCC) (a mechanism of cell-mediated immune defense whereby cells that have antibodies attached to their surfaces are targeted for lysis) (104).…”
Section: B Cells and Antibodiesmentioning
confidence: 99%
“…However, even though anti-Chlamydia antibodies are able to neutralize infection in vitro (100,101), growing evidence shows that B cells may not be important for initial chlamydial infection but, instead, play an important role in the secondary memory response (102,103). Several possible mechanisms by which B cells modulate immunity during reinfection include antibody-mediated neutralization and opsonization (100) and antibody-dependent cellular cytotoxicity (ADCC) (a mechanism of cell-mediated immune defense whereby cells that have antibodies attached to their surfaces are targeted for lysis) (104).…”
Section: B Cells and Antibodiesmentioning
confidence: 99%
“…Subunit antigen vaccines represent the bulk of vaccine studies, and vaccines based on combinations of a number of chlamydial antigens, adjuvants, and delivery systems have had various degrees of success in preventing infection (8,22,62). Chlamydial antigens, including secreted proteins, such as chlamydial protease-like activity factor (CPAF) (16,33,(43)(44)(45)(46), and membrane associated proteins, such as PorB (26,30) and IncA (33), have also been used in subunit vaccines; however, the vast majority of studies have focused on the major outer membrane protein (MOMP), an immunodominant antigen in both human and animal studies (22,62). Novel delivery systems, including Vibrio cholerae ghosts and cationic liposomes, have been introduced into chlamydial vaccine research, and while initial studies have shown incomplete protection, these systems may have the potential to elicit protective responses against chlamydial genital infection when used in conjunction with appropriate antigens (2,19,20,23).…”
mentioning
confidence: 99%
“…Seminal fluid is also reportedly a mechanism of microbial transfer to the female upper genital tract. Furthermore, some microorganisms have the propensity to attach to the surface of spermatozoa, whilst others are obligate intracellular parasites within the spermatozoa C. trachomatis, N. gonorrhoeae, Mycoplasma spp., Ureaplasma spp., and E. coli have all been shown to adhere to the surface of spermatozoa or form intracellular inclusions within the spermatozoa (Friberg et al, 1987;Hickey et al, 2009;James-Holmquest et al, 1974;Murthy et al, 2009;Sanchez et al, 1989;Wolner-Hanssen & Mardh 1984). Further, female partners of infected men with spermatozoa in their ejaculate had a significantly higher incidence of upper genital tract infection compared to infected men who have been vasectomised (Toth et al, 1984).…”
Section: Upper Genital Tract Infectionsmentioning
confidence: 99%
“…These have recently been reviewed by several groups (Cochrane et al, 2010;Farris & Morrison 2011;Hafner 2007;Hafner & McNeilly 2008;Lyons et al, 2006;Miyairi et al, 2010;Rank & Whittum-Hudson 2010). These animal models have proved invaluable in providing knowledge of many novel candidate antigens for a vaccine (Barker et al, 2008;McNeilly et al, 2007;Murthy AK et al, 2011;Murthy et al, 2009) as well as novel delivery vehicles (Xu et al, 2011) and delivery routes such as oral and transcutaneous immunization for protection of genital infections (Hickey et al, 2010;Hickey et al, 2009) and have investigated a myriad of potential adjuvants (reviewed in Cochrane et al, 2010;Farris and Morrison, 2011; and immune responses elicited following animal immunization trials (Cunningham et al, 2011;McNeilly et al, 2007;Patton et al, 1983). For example it has recently been reported that a Vibrio cholerae ghost (VCG) multisubunit chlamydial vaccine delivered to mice by the intramuscular route stimulated immune memory in these animals (Eko et al, 2011).…”
Section: Chlamydia and Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation